The policies and strategies for prevent and control non-communicable diseases: A bibliometric analysis of global research trends - Itsnatur Rizkiyah Apriliyanti; Yosua Darmadi Kosen (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Reducing premature mortality from non-communicable diseases (NCDs) is a key target of the Sustainable Development Goals (SDGs). This study aimed to map global research trends about policies and strategies for the prevention and control of NCDs using a bibliometric approach. Methods: A bibliometric analysis was conducted using the Scopus database. Articles published in English between 1 January 2023 and 6 November 2025 were retrieved. Bibliometric networks of authors, institutions, countries, sources, keywords, and co-cited references were analyzed and visualized using VOSviewer. Findings: A total of 555 articles were included. The field is dominated by collaborative networks of authors and institutions from high-income countries, particularly the United States, the United Kingdom, Australia, and Iran. The Lancet and other leading journals in public health and medicine formed the main co-citation hubs. Frequently co-occurring keywords highlighted policy implementation, health systems, risk factors, health promotion, and prevention and control strategies for major NCDs. Conclusion: Global research on NCD policies and strategies is increasing, yet remains concentrated in high-income settings. Future studies should prioritize implementation and evaluation of NCD policies in low- and middle-income countries, integration of digital health technologies, development of context-specific risk-based strategies, and assessments of policy impacts on health and economic inequalities. Novelty/Originality of this article: This study provides one of the first up-to-date bibliometric overviews (2023–2025) of global publications on NCD prevention and control policies and strategies, offering evidence-based directions for future research and policymaking.